Passing. Anatomies and Physiologies of Identity Transformations - MUDURE, Mihaela; NANDA, Aparajita (2024)
As an identity shift that has existed for centuries, passing is astrategy to change one’s perceived identity that cannot beseparated from colorism, or the preference for individualsexhibiting European-like bodily features. The results of thepsychological study of colorism undertaken by Crutchfield etal. show that this predilection is a “historical trauma response[that] not only incorporates subjugation of oppressed AfricanAmericans, but can also incorporate resistance” (826). Passingcan send mixed messages where oppression contaminatesresistance and vice versa.